Photovoltaic Power Plant Installation Variants and Their Strategic Adoption in India’s Electricity Sector for Creating Sustainable Communities - Bairagi, Prashant Kumar (Digital Repository of Theses - SSBM Geneva, 2025)
The transition to renewable energy is a cornerstone of global efforts to combat climate change and promote sustainable development. This thesis investigates the strategic adoption of photovoltaic (PV) power plant installation variants within India's electricity sector to foster sustainable communities. Recognizing India's significant solar energy potential and its unique socio-economic and infrastructural challenges, the research employs a comparative analysis of various PV installation types, including rooftop solar, ground-mounted plants, and emerging technologies like floating solar. Through case studies, stakeholder interviews, and secondary data, the study evaluates the efficiency, cost-effectiveness, and environmental impact of these systems across diverse Indian contexts. The findings reveal that strategic PV deployment can significantly reduce energy costs, enhance energy security, mitigate carbon emissions, and stimulate economic growth, particularly in underserved regions. However, challenges such as high initial capital costs, regulatory hurdles, and uneven policy implementation are also highlighted. To address these issues, the thesis proposes a multi-stakeholder framework integrating financial innovations, tailored policy interventions, and community-centric approaches to maximize the socio-economic and environmental benefits of solar energy adoption. This research contributes actionable insights for policymakers, energy practitioners, and community leaders aiming to leverage solar energy to achieve India's renewable energy targets and the UN Sustainable Development Goals (SDGs).